The Moon is Down Publicity Still - 20th Century Fox:::Creator::::::::::::
The Moon Is Down publicity still from National Television Associates. Lee Cobb (Doctor Albert Winter), Henry Travers (Mayor Orden), Margaret Wycherly (Sarah Orden.) Digital copy only. Hard copy held in ephemera collection.